The Evolving Learner: Educational Psychology’s Perspectives on Growth and Development - Darbani, Seyed Ali; Atapour, Neda (KMAN Counseling & Psychology Nexus, 2023)
This article aims to explore the multidimensional influences on learner development within educational psychology, focusing on learner autonomy, engagement, the impact of technology, and the integration of cultural diversity in educational settings. A narrative review method was utilized, synthesizing studies from various educational contexts. This included an analysis of learner interaction, motivational psychology, adaptive learning systems, and the integration of digital technologies in education. The review reveals that learner autonomy, engagement, and the effective use of technology significantly contribute to learner development. Additionally, cultural diversity and social-emotional learning play crucial roles in shaping educational outcomes. Emerging technologies such as AI, AR, and VR show potential in enhancing learning experiences. The article concludes that educational practices are evolving towards being more learner-centered and technology-enhanced. It emphasizes the importance of adaptive learning environments and suggests future research directions in educational technology and pedagogy to support holistic learner development.